Preserved C-peptide secretion is associated with fewer low-glucose events and lower glucose variability on flash glucose monitoring in adults with type 1 diabetes - Gibb, Fraser W. (Diabetologia, 2020)
AIMS/HYPOTHESIS: We aimed to assess whether persistence of C-peptide secretion is associated with less glucose variability and fewer low-glucose events in adults with type 1 diabetes who use flash monitoring. METHODS: We performed a cross-sectional study of 290 adults attending a university teaching hospital diabetes clinic, with type 1 diabetes, who use flash monitoring and in whom a random plasma C-peptide was available in the past 2 years. Variables relating to flash monitoring were compared between individuals with low C-peptide (<10 pmol/l) and those with persistent C-peptide (either 10–200 pmol/l or 10–50 pmol/l). In addition, the relationship between self-reported hypoglycaemia and C-peptide was assessed (n = 167). Data are median (interquartile range). RESULTS: Individuals with preserved C-peptide secretion (10–200 pmol/l) had shorter duration of diabetes (15 [9–24] vs 25 [15–34] years, p < 0.001) and older age at diagnosis (23 [14–28] vs 15 [9–25] years, p < 0.001), although current age did not differ in this cohort. Preserved C-peptide was associated with lower time with glucose <3.9 mmol/l (3% [2–6%] vs 5% [3–9%], p < 0.001), fewer low-glucose events per 2 week period (7 [4–10] vs 10 [5–16], p < 0.001), lower SD of glucose (3.8 [3.4–4.2] vs 4.1 [3.5–4.7] mmol/l, p = 0.017) and lower CV of glucose (38.0 [35.0–41.6] vs 41.8 [36.5–45.8], p < 0.001). These differences were also present in those with C-peptide 10–50 pmol/l and associations were independent of diabetes duration and estimated HbA(1c) in logistic regression analysis. Preserved C-peptide was also associated with lower rates of self-reported asymptomatic hypoglycaemia (8.0% vs 22.8% in the past month, p = 0.028). CONCLUSIONS/INTERPRETATION: Preserved C-peptide secretion is associated with fewer low-glucose events and lower glucose variability on flash monitoring. This suggests that individuals with preserved C-peptide may more safely achieve intensive glycaemic targets. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-020-05099-3) contains peer-reviewed but unedited supplementary material, which is available to authorised users.